МОДУЛЬНО-РЕЙТИНГОВА СИСТЕМА ОЦІНЮВАННЯ ЗНАНЬ УЧНІВ (Педагогіка вищої та середньої школи, 2022)
In Permjakova Alexander Anatoljevicha and Zelenkovoj Natalia Ivanovny's clause theoretical questions of a modul-rating estimation of knowledge ofpupils of modem school are considered.